Biological stress reactivity as an index of the two polarities of the experience model. (October 2017) - Silva, Jaime R.; Vivanco-Carlevari, Anastassia; Barrientos, Mauricio; Martínez, Claudio; Salazar, Luis A.; Krause, Mariane
Highlights: There is a physiological correlate of the polarities of experience model. The introjective group presents high biological reactivity to stress in contrast to the anaclitic group. The anaclitic group tends to presents a high perception of stress in contrast to the introjective group. The article opens the question as to how to conceptualize the stress response system on the polarities of experience model. Abstract: The two-polarities model of personality argues that experience is organized around two axes: interpersonal relatedness and self-definition . Differential emphasis on one of these poles defines adaptive and pathological experiences, generating anaclitic or introjective tendencies. The anaclitic pattern, on one hand, has been conceptually related with an exaggerated emphasis on interpersonal relatedness. On the other hand, the introjective pattern has been connected to high levels of self-criticism. The aim of this study was to investigate the psychophysiological basis for this relationship. Specifically, we hypothesized that the anaclitic individual should have a higher biological reactivity to stress (BRS), measured by the cortisol concentration in saliva, in an interpersonal stress induction protocol (Trier Social Stress Test). Contrary to what was expected, the results indicated that introjective participants presented a higher BSR than the anaclitic group. Interestingly, in contrast to their higher BSR, the introjective group reported a diminished subjective stress in relation to the average. In the anaclitic group, a tendency that goes in the opposite direction was found. Theoretical implications of these findings were discussed.